Variation in Growth Traits of Ironwood (Eusideroxylon zwageri T. ET B.) Progeny Trial in Bondowoso - Prastyono, Prastyono; Susanto, Mudji Susanto (Jurnal Wasian, 2015)
The estimation of genetic parameters for stem diameter and plant height of ironwood (Eusideroxylon zwageri T. et B.) was conducted in a progeny trial in Bondowoso, East Java at the age of 5,5 years. The trial was arranged in an incomplete block design, which comprised of 49 families from three provenances (Batanghari, Berau and Kutai Kertanegara) with 4 replications and single tree plot. Families of Batanghari provenance showed the best growth of stem diameter and plant height compared with another provenance. There was significant difference in plant height between families within provenance, whereas stem diameter was not significantly different both of between provenance as well as between families within one provenance. Non-genetic or environmental factors provide considerable influence on plant growth in the progeny test of ironwood until the age of 5.5 years; it was indicated by the residual variance component. Individual heritability for plant height was considered as high (0.37) and stem diameter was considered as moderate (0.26). There was a strong genetic correlation between the stem diameter and plant height (0.95). This information is very important for future genetic improvement of ironwood.